PARP-1 involvement in neurodegeneration: A focus on Alzheimer's and Parkinson's diseases. (March 2015) - Martire, Sara; Mosca, Luciana; d'Erme, Maria
Graphical abstract: Abstract: DNA damage is the prime activator of the enzyme poly(ADP-ribose)polymerase1 (PARP-1) whose overactivation has been proven to be associated with the pathogenesis of numerous central nervous system disorders, such as ischemia, neuroinflammation, and neurodegenerative diseases. Under oxidative stress conditions PARP-1 activity increases, leading to an accumulation of ADP-ribose polymers and NAD + depletion, that induces energy crisis and finally cell death. This review aims to explain the contribution of PARP-1 in neurodegenerative diseases, focusing on Alzheimer's and Parkinson's disease, to stimulate further studies on this issue and thereby engage a new perspective regarding the design of possible therapeutic agents or the identification of biomarkers.